2022
DOI: 10.31083/j.jin2103079
|View full text |Cite
|
Sign up to set email alerts
|

The influence of electronic acupuncture at a specific frequency in facilitating the passage of NGF through the blood-brain barrier and its effect on learning and memory in MCAO/R rats

Abstract: Background:The blood-brain barrier (BBB) maintains the balance of the internal environment of the brain and strictly controls substance exchange between the brain and blood dynamically but stably. Transient increases in the permeability of the BBB plays an important role in helping macromolecular drugs enter the brain to exert their pharmacological effects. Previous research has revealed that electronic acupuncture (EA) stimulation connecting Baihui (GV20) and Shuigou (GV26) at a specific frequency can enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…In this study, we observed that serum LPS and DAO levels were higher in the APP/AP1‐C and WT‐C groups than in groups that received EA intervention, indicating gut barrier impairment (Du et al, 2019). Interestingly, our study detected the preserved integrity of both the intestinal barrier and BBB in APP/PS1‐E mice, which are consistent with the findings of Wang et al (2020) and Zhao et al (2022). Tight junction protein levels and electron microscopy results revealed that the BBB was destroyed in the absence of EA and the concentration of inflammatory factors was increased in the hippocampal tissue.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed that serum LPS and DAO levels were higher in the APP/AP1‐C and WT‐C groups than in groups that received EA intervention, indicating gut barrier impairment (Du et al, 2019). Interestingly, our study detected the preserved integrity of both the intestinal barrier and BBB in APP/PS1‐E mice, which are consistent with the findings of Wang et al (2020) and Zhao et al (2022). Tight junction protein levels and electron microscopy results revealed that the BBB was destroyed in the absence of EA and the concentration of inflammatory factors was increased in the hippocampal tissue.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we first verified the role of EA, and the previous research group also found that opening BBB by EA could induce NGF to enter the brain tissue of rats and improve the learning and memory ability of MCAO/R model rats [6], and started to conduct clinical experimental observation on the sequelae of cerebral apoplexy. Therefore, the experiment was conducted 4 weeks after the animal modeling to ensure the complete repair of BBB, which was also in line with the clinical practice of sequelae of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 69%
“…Modern studies have shown that these two acupoints have a regulatory effect on the central nervous system and have the potential to be widely used in the treatment of brain-derived diseases [5]. The results of previous studies have indicated that administration of EA (EA) with certain parameters, specifically 2/100 Hz, 3 mA, and 6 s/6 s, for 40 min, stimulates these two points in rats to effectively open the BBB, allowing Evans Blue (EB) and nerve growth factor (NGF) to enter the brain tissue [6]. It has been found that after EA stimulation, neurons in the brain were activated, and the expression of tight junction (TJ) proteins such as Occludin and zona occludens-1 (ZO-1) was significantly lower [7].…”
Section: Introductionmentioning
confidence: 99%
“…A fixed frequency of 2 or 100 Hz may show easy adaptability and a relatively continuous and stable stimulation, which may reduce the effect of EA [ 143 ]. Therefore, 2/100 Hz EA was applied to the GV20 and GV26 acupoints for 40 min, effectively increasing BBB permeability in rats [ 144 ]. However, for hippocampal synaptic transmission, high-frequency EA could demonstrate a better effect in rats with Alzheimer's disease [ 145 ].…”
Section: How To Improve the Effect Of Acupuncturementioning
confidence: 99%
“…Acupuncture can upregulate vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 2 (VEGFR2), basic fibroblast growth factor (bFGF), and CD34 + , thereby promoting the proliferation of vascular endothelial cells, increasing local cerebral blood flow, activating multiple signaling pathways, and mediating vascular and nerve regeneration [ 158 ]. EA stimulation of “Baihui” (GV20) and “Shuigou” (GV26) at a specific frequency has been reported to increase the permeability of BBB, providing a strategy for the treatment of nervous system diseases [ 143 , 144 ]. Liu et al [ 111 ] found that EA could regulate the expression of VEGF genes and promote angiogenesis in the ischemic cerebral cortex, which may play an important role in the improvement of CI in ischemic stroke.…”
Section: Vascular–glia–neuron Unit Might Be a Critical Target For Acu...mentioning
confidence: 99%